Neuromotor adaptations in people with Parkinson's Disease following a 12-month multimodal non-contact boxing intervention - King, Adam C.; Carr, Joshua C.; Voskuil, Caleb; Chen, Kuanting; Porter, Ryan R.; Thijs, Zoe; Watts, Christopher R. (Frontiers in Human Neuroscience, 2026)
Parkinson's Disease (PD) is a common neurological disorder that diminishes neuromotor control. Exercise training provides a nonpharmacological treatment option that may help motor symptom severity and trajectory. In the present case series, we assessed linear and non-linear measures of neuromotor control along with functional measures of mobility in six men living with PD across a year of multimodal exercise training. Our measurements encompassed mobility, balance, strength, and force control metrics and were captured at baseline as well as at defined intervals following exercise engagement. The results appear to indicate a favorable preservation of functional ability and neuromotor control for most of the cohort across the yearlong exercise intervention. Our linear measures of neuromotor control generally remained stable with slight improvements from baseline to month 12, with visually distinct trends for our non-linear measures (Sample Entropy) of neuromotor control suggestive of more adaptive motor control strategies for both postural and force control. These data corroborate reports showing favorable outcomes for people with Parkinson's Disease following exercise engagement. Our year-long assessment of neuromotor control in a cohort of men with Parkinson's disease provides a novel contribution to the trajectory of change in this population while undergoing multimodal exercise training.